2017
DOI: 10.1007/s11192-016-2230-9
|View full text |Cite
|
Sign up to set email alerts
|

Growth of international collaboration in science: revisiting six specialties

Abstract: International collaboration in science continues to grow at a remarkable rate, but little agreement exists about dynamics of growth and organization at the discipline level. Some suggest that disciplines differ in their collaborative tendencies, reflecting their epistemic culture. This study examines collaborative patterns in six previously studied specialties to add new data and conduct analyses over time. Our findings show that the global network of collaboration continues to add new nations and new particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(94 citation statements)
references
References 46 publications
(40 reference statements)
4
76
0
5
Order By: Relevance
“…We chose fields to reflect a range of referencing behavior, from astrophysics, which has high citing activity, to mathematics, which has low citing activity. We replicated the analysis for six scientific specialties that were analyzed in previous research (Wagner, Whetsell, & Leydesdorff 2017) using WoS data. At this disciplinary level, the results were either non-significant or they supported the main results in Table 4.…”
Section: Disciplinary Affectsmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose fields to reflect a range of referencing behavior, from astrophysics, which has high citing activity, to mathematics, which has low citing activity. We replicated the analysis for six scientific specialties that were analyzed in previous research (Wagner, Whetsell, & Leydesdorff 2017) using WoS data. At this disciplinary level, the results were either non-significant or they supported the main results in Table 4.…”
Section: Disciplinary Affectsmentioning
confidence: 99%
“…showed that internationally coauthored articles were cited two times the rate of ones from a single country. Wagner et al (2017) examined international collaborations in six scientific disciples showing that a rise in the number of countries-per-article was also linked to higher citations. The number of countries per article is also shown to be significant for increased citations (Didegah & Thelwall, 2013;Wagner et al, 2017).…”
Section: -Introductionmentioning
confidence: 99%
“…A tudomány felgyorsult globalizációjának köszönhetően a nemzetközi tudományos együttműködés napjainkra egyre kiterjedtebbé válik (Luukkonen et al 1993;The Royal Society 2011;Wagner, Whetsell, Leydesdorff 2017). Luukkonen et al (1993) szerint a nemzetközi tudományos együttműködést számos tényező motiválja, többek között a vágy a tudás növelésére, a tapasztalatok és adatok kicserélésének szükségessége, a törekvés a szakmai fejlődésre.…”
Section: A Kelet-közép-európai Országok Együttműködési Mintázataiunclassified
“…Instruments with different measurement purposes are often used together to produce a better understanding of the underlying process being measured [6,7]. This is becoming common as collaborations between different scientific institutes are increasing [8]. With the proliferation of Internet and Internet of Things (IoT) devices, information is now expected to be available with only a few clicks [9].…”
Section: Introductionmentioning
confidence: 99%